2020
DOI: 10.3390/e22111305
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative Structures, Organisms and Evolution

Abstract: Self-organization in nonequilibrium systems has been known for over 50 years. Under nonequilibrium conditions, the state of a system can become unstable and a transition to an organized structure can occur. Such structures include oscillating chemical reactions and spatiotemporal patterns in chemical and other systems. Because entropy and free-energy dissipating irreversible processes generate and maintain these structures, these have been called dissipative structures. Our recent research revealed that some o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 64 publications
0
33
0
Order By: Relevance
“…There is also an issue of whether life's origin (less so its meaning) might have something to do with dissipative structures of the kind that Prigogine [125] described. Dissipative structures are discussed in the context of the origin of physicochemical order, as in Zhabotinsky reactions, and in the context of life [126]. Though skeptical that life could be seen as belonging to a category that would fall under the label of dissipative structures, we can say that living cells might have some properties in common dissipative structures, as the latter only arise in far from equilibrium systems, whereby both living things and H 2 -producing hydrothermal vents are far from equilibrium systems.…”
Section: Discussionmentioning
confidence: 99%
“…There is also an issue of whether life's origin (less so its meaning) might have something to do with dissipative structures of the kind that Prigogine [125] described. Dissipative structures are discussed in the context of the origin of physicochemical order, as in Zhabotinsky reactions, and in the context of life [126]. Though skeptical that life could be seen as belonging to a category that would fall under the label of dissipative structures, we can say that living cells might have some properties in common dissipative structures, as the latter only arise in far from equilibrium systems, whereby both living things and H 2 -producing hydrothermal vents are far from equilibrium systems.…”
Section: Discussionmentioning
confidence: 99%
“…Because entropy and free-energy dissipating irreversible processes generate and maintain these structures, these have been called dissipative structures.' (Kondepudi et al, 2020). In short, the presentment of the opportunity in a nonequilibrium state triggers self-organization and actions from the entrepreneurs who will move to dissipate the potential gradient existing in the opportunity to produce a lower entropy state and a stabler system with profit derived.…”
Section: Discussionmentioning
confidence: 99%
“…In short, the presentment of the opportunity in a nonequilibrium state triggers self-organization and actions from the entrepreneurs who will move to dissipate the potential gradient existing in the opportunity to produce a lower entropy state and a stabler system with profit derived. In the study in (Kondepudi et al, 2020) their research revealed that some of these structures exhibit organism-like behaviour akin to the organism-like behaviours in electrically and chemically driven systems. This can be a breakthrough discovery as the behaviours of entrepreneurs is part of pattern formation responding to signals and stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The release of increasing entropy in the environment is highly facilitated, as the external world is much wider and bigger than a biological object. The increase in entropy outside the system pushes onward the system to go ahead in replicating patterns and creating order [ 64 , 65 , 66 ]. In this sense it goes on dissipating contrasting forces until the system is “frozen” (somehow) in a highly ordered state, where, more frequently, it starts to operate not far from the thermodynamic equilibrium.…”
Section: Chance Necessity and Dissipation: The Concept Of “Nothimentioning
confidence: 99%